2011
DOI: 10.4238/2011.december.14.1
|View full text |Cite
|
Sign up to set email alerts
|

RAPD analysis of the genetic diversity of mango (Mangifera indica) germplasm in Brazil

Abstract: ABSTRACT. We evaluated genetic variability of mango (Mangifera indica) accessions maintained in the Active Germplasm Bank of Embrapa Meio-Norte in Teresina, Piauí, Brazil, using RAPDs. Among these accessions, 35 originated from plantings in Brazil, six from the USA and one from India. Genomic DNA, extracted from leaf material using a commercial purification kit, was subjected to PCR with the primers A01, A09, G03, G10, N05, and M16. Fifty-five polymorphic loci were identified, with mean of 9.16 ± 3.31 bands pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…In the dendrogram, the most similar accessions were Keitt mango (accession 19,20) and Banana mango (accession 1, 2). The most divergent were Keitt mango (accession 19) and Maçã mango (accession 14), different from those given by the Ward method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dendrogram, the most similar accessions were Keitt mango (accession 19,20) and Banana mango (accession 1, 2). The most divergent were Keitt mango (accession 19) and Maçã mango (accession 14), different from those given by the Ward method.…”
Section: Resultsmentioning
confidence: 99%
“…This variability was most intense between the different varieties studied, as accessions of the same variety remained within the same group. There have been several works on the genetic diversity of mangos that particularly used molecular markers [17][18][19]. The evaluation of genetic diversity through morphological characteristics has also been widely employed in studies [8,20].…”
Section: Accessionsmentioning
confidence: 99%
“…For example, Adawy et al (2004) and Hussein et al (2005) found that RAPD polymorphism rate in various Egyptian date palm cultivars (Phoniex dactylifera L.) is in the range of 25.2% and for ISSR technique in the range of 28.6%. Among the studied Pistacia vera (L.) various cultivars polymorphism rate based on ISSR markers was 46.4% and 100% among Mangifera indica (L.) based on ISSR markers (Noroozi et al, 2009;Souza et al, 2011). RADP, mixed RAPD and ISSR showed various degrees in their ability to detect the diversifications among populations of S. molle plants.…”
Section: Discussionmentioning
confidence: 98%
“…Genetic variability in mango cultivars can ultimately lead to differences in carotenoids (Mitra, 1997) and anthocyanin (Lizada, 1991) content. Souza et al (2011) reported that certain Brazilian mango cultivars have genomic similarities of as little as 7% showing a significant genetic diversity that could contribute to phytochemical differences between mango fruit cultivars. These phytochemical different cultivars offer potential in diverse uses, including in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Mango is regarded as a valuable source of phytochemical compounds (Kim et al, 2007;Ashoush and Gadallah, 2011;Mudau et al, 2013); among these compounds, polyphenolics are widely distributed secondary metabolites and the predominant antioxidants present. Several studies have reported phenolic compounds in mango flesh and peels, including various flavonoids, xathones, phenolic acids and gallotannins (Schieber et al, 2000;Berardini et al, 2005) and variability of these compounds have been observed in different mango cultivars (Souza et al, 2011;Taing et al, 2012).…”
Section: Al 2011)mentioning
confidence: 99%